SRIHARJO PADA MASA KRISIS - Pande Made Kutanegara (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1999)
Generally, it is assumed that the economic crisis would hardly experienced by people who live in urban areas, mainly those who are in the lowest social stratum. Certainly, some people (experts) are convinced that people who live in the village would not affected by the impact of stagnating national economy. Recent studies, however, show that almost all of social stratum in Indonesia, both in cities and villages, are hit by the crisis but the intensities of its varies from one group to another. There are many factors to be considered in discussing impacts of crisis, i.e social, economy, and demography, as well. This article will clearly describe how people from various strata in the village perceive and how do they cope with the crisis.